How to Read Uncommon Names in Present-Day Japan: A Guide for Non-Native Japanese Speakers - Ogihara, Yuji (Frontiers in Communication, 2021)
A previous study categorized uncommon names in present-day Japan. However, it was presented in Japanese mainly for native Japanese speakers and thus failed to explain shared knowledge about naming practices, making it difficult for non-native Japanese speakers to understand the study. It is important to share cultural practices not only within but also beyond the culture. Moreover, considering that Japanese names are difficult to read, reducing the risk of failing to read names correctly is helpful especially for non-native Japanese speakers. Therefore, by adding supplementary explanations, this paper systematically describes the characteristics and patterns of uncommon names in present-day Japan. Uncommon names largely take two forms: names with an uncommon reading of Chinese characters and names with uncommon Chinese characters. Regarding the reading, there are three types: 1-1) names that abbreviate the common reading of Chinese characters, 1-2) names that are pronounced as a foreign word, and 1-3) names that are pronounced based on the meaning/image of Chinese characters. Regarding the writing, there are two types: 2-1) names with Chinese characters used infrequently and 2-2) names with silent Chinese characters adding to the semantic meaning without contributing to the pronunciation. Further, a combination of these methods makes names more unique.